Students’ Readiness and Perceptions towards Outcome-Based Education Implementation in Higher Education Institutions - Subin Thomas; Jeena Joseph; Chellappan Santhakumary Anuja; Sarada Mohanachandran Anitha (Praxis & Saber)
The new education policy in India proposes a paradigm shift to mold graduates who meet the latest industry requirements. Outcome-Based Education (OBE), a key principle of this policy, ensures the attainment of essential skills, measurable learning outcomes, and global competitiveness. OBE provides a framework for developing program and course outcomes, and accreditation systems require institutions to adopt this model. With many universities and higher education institutions in India implementing OBE, it is essential to analyze students’ experiences in this process. This study explores the factors contributing to OBE implementation in Higher Education Institutions in Kerala. A quantitative, cross-sectional survey was conducted with 369 students from engineering and management programs in central Kerala. Constructs such as student readiness, motivation, faculty engagement, perception, perceived outcomes, and management support were examined. Smart PLS software was used to evaluate construct validity and model fitness. Results showed a significant positive impact of student perception and perceived outcome on readiness. However, management support had an insignificant moderating role. These findings suggest that strengthening management support may enhance OBE implementation effectiveness.